PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS MELALUI MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE - Arnidha, Yunni (JURNAL E-DUMATH, 2016)
This study aims to analyze the improvement of studentsâ mathematicalrepresentation achievement taught by cooperative learning think pair share andstudentsâ mathematical representation achievement taught by conventional method.This study is quasi experimental with Pretest âPosttest Control Group Design. Thisstudy conducted at SMPN 3 Pringsewu. The population was all of the eight gradestudents at SMPN 3 Pringsewu, with the samples of this study consists of the VIII-2class as the experiment class and VIII-5 class as the control class. To obtain thedata, it used mathematical representation achievement test instrument. The dataanalysis was conducted to know the average difference between two samples usingt-test. The result showed the improvement of mathematical representationachievement taught by cooperative learning think pair share is better than thestudents taught by conventional learning method.Keywords: think pair share model, conventional learning method,Mathematical representation